Numbers and Numeracy in the Greek Polis - Sing, Robert; Osborne, Robin; Berkel, Tazuko van (Mnemosyne, Supplements, 2022)
We tend to think of numbers as inherently objective and precise. Yet the diverse ways in which ancient Greeks used numbers illustrates that counting is actually shaped by context-specific and culturally-dependent choices: what should be counted and how, who should count, and how should the results be shared? This volume is the first to focus on the generation and use of numbers in the polis to quantify, communicate and persuade. Its papers demonstrate the rich insights that can be gained into ancient Greek societies by reappraising seemingly straightforward examples of quantification as reflections of daily life and cultural understandings.